Empowering the Community in Building a Culture of Character, Awareness Love History and Innovation Entrepreneurship in students of Madrasah Aliyah State School 1 Deli Serdang - Pujiati,; Ramli,; Nasution, Khairina; Iskandarini, (Journal of Saintech Transfer, 2024)
Empowering the community in building a culture of character, awareness love history and innovation entrepreneurship in students of Madrasah Aliyah State School 1 Deli Serdang is to develop the potential of students in terms of culture of character, historical knowledge and entrepreneurial skills. Some of the specific goals that can be achieved include increasing students' awareness of the importance of building a culture of good character, such as integrity, discipline, responsibility and honesty. Enhance students' knowledge of history, both national and local history, as well as increasing their love for the cultural heritage and history of the nation. The methods used in achieving the goals are character education through extracurricular pursuits, academic instruction, and self-improvement initialisms. Entrepreneurship training, organizing training and entrepreneurial workshops involving business practitioners and successful entrepreneurs as guest speakers. In addition, students may be given the opportunity to develop their own business ideas through entrepreneurship competitions or incubation program. The use of technology, using information and communication technology in the learning process to enhance students' interest in studying history and developing entrepreneurial skills. The dedication of this community service can raise public awareness of love of history and develop the skills of entrepreneurs at Madrasah Aliyah State School 1 Deli Serdang.